2018
DOI: 10.3324/haematol.2018.206383
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic immune response to therapeutic factor VIII: exacerbated response or failed induction of tolerance?

Abstract: Therapeutic factor VIII is highly immunogenic. Despite intensive research in the last decades, the reasons why 5-30% of patients with hemophilia A (of all severities) develop inhibitory anti-factor VIII antibodies (inhibitors) following replacement therapy remain an enigma. Under physiological conditions, endogenous factor VIII is recognized by the immune system. Likewise, numerous observations indicate that, in hemophilia A patients without inhibitors, exogenous therapeutic factor VIII is immunologically asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…The infused clotting factor is perceived by the immune system as a foreign protein and as such it is hard to demonstrate a contributing effect of a danger signal. In a recent published paper, it even proposes that all hemophilia A patients develop anti-FVIII immune responses regardless the presence of danger signals and that particularly the ability to develop counteractive tolerogenic reactions determines if a patients will develop clinically significant inhibitors or not [86].…”
Section: Resultsmentioning
confidence: 99%
“…The infused clotting factor is perceived by the immune system as a foreign protein and as such it is hard to demonstrate a contributing effect of a danger signal. In a recent published paper, it even proposes that all hemophilia A patients develop anti-FVIII immune responses regardless the presence of danger signals and that particularly the ability to develop counteractive tolerogenic reactions determines if a patients will develop clinically significant inhibitors or not [86].…”
Section: Resultsmentioning
confidence: 99%
“…The uptake of blood coagulation FVIII by antigen presenting cells has been studied intensively in the last decade. Most of these studies have been performed in model systems like human monocyte-derived dendritic cells as well as mouse bone marrowderived dendritic cells (32)(33)(34). In parallel, immuno-localization of FVIII in the spleen following its infusion into mice has generated very interesting findings on the topology of FVIII association with, and possibly uptake by, different populations of antigen presenting cells in specific niches within the splenic architecture (Figure 1).…”
Section: Fviii Uptake Processing and Presentationmentioning
confidence: 99%
“…Lastly, an alternative hypothesis has suggested that inhibitor development must result from ineffective tolerance induction to FVIII rather than being primarily driven by environmental signals or antigen fluctuations (Varthaman & Lacroix‐Desmazes, ). Unfortunately, whether FVIII‐specific tolerance is generated primarily due to central or peripheral mechanisms is still unresolved.…”
Section: Theories Of Inhibitor Formationmentioning
confidence: 99%